Structural characterization of AlCuFe icosahedral quasicrystal nanoparticles synthesized using femtosecond laser ablation - Singh B.K.; Banerjee D.; Mangababu A.; Shadangi Y.; Mukhopadhyay N.K.; Rawat R.; Pathak A.P.; Rao Soma V.; Tiwari A.; Tripathi A. (My University, 2025)
The AlCuFe icosahedral quasicrystal (IQC) targets prepared using two different methods- (1) vacuum induction melting followed by annealing, and (2) spray forming, have been subjected to femtosecond laser ablation in deionized water (DI water) for 54 min. High-resolution transmission electron microscopy (HRTEM) and selected area electron diffraction (SAED) pattern analysis of the synthesized nanoparticles (NPs) revealed the presence of IQC phases. NPs obtained from the induction-melted IQC target contained Al13Fe4 and β-Al(Fe,Cu) phases along with the IQC phase, reflecting the phase composition of the bulk target. In contrast, NPs from the spray-formed target exhibited only the IQC phase. Both samples also showed the presence of CuO and amorphous Al2O3. The ablated region of the target surface showed the formation of grooves and bumps. In addition, the formation of liquid vortices during the ablation process was ascertained by the presence of macropores in the ablated region of the target’s surface. I-V plots obtained from the ablated region and the non-ablated region of the target’s surface revealed an increase in the resistance post-ablation. This increase is attributed to the presence of defects and surface oxidation that incurred during the laser irradiation. © The Author(s), under exclusive licence to Springer Science+Business Media, LLC, part of Springer Nature 2024.